An Analysis of Lady Christian Nimmo’s Characteristics in Kate Foster’s The Maiden through Maslow’s Hierarchy of Needs - Hartawan, Ni Putu Zefanya Putri Gracia; Sriastuti, Anna (STIBA IEC JAKARTA, 2025)
This study employs Maslow's Hierarchy of Needs to analyze the characteristics of Lady Christian Nimmo in Kate Foster's The Maiden to identify the levels in Maslow's pyramid that the main character most and least fulfills, as well as how those fulfillments influence the main character's round characteristics. The qualitative descriptive approach was used to collect the data for this study, and the results were obtained by applying close reading. According to this study, the female main character's character development is also impacted by the connections between the five levels of Maslow's Hierarchy of Needs. This study shows that even when the need for security is met, it does not ensure that the subsequent needs—love and belonging—are also met. Lady Christian's experience, in which she receives security but not love and belonging, impacts her self-esteem and ultimately prevents her from reaching self-actualization. It will afterward emphasize certain characteristics of the character development that the story's female lead has gone through, namely noble, intimate, free-spirited, brave, confident, and vulnerable.